Does banning affirmative action hurt racial diversity? - PARK, Youjeong (KDI School, 2024)
Affirmative action in U.S. university admissions aims to enhance student racial diversity and address educational inequities. However, 11 states have banned affirmative action in university admissions. This study examines the effects of these bans on student racial diversity across U.S. public universities from 1990 to 2020. I find that banning affirmative action has reduced undergraduate racial diversity. Specifically, there is a sharp rise in Hispanic enrollment shares while Asian, Black, and White enrollment shares remain unchanged. Furthermore, the study explores how state legislature partisanship creates variations in policy effects, showing that Asian enrollment shares have decreased in Democratic-led states. The results provide U.S. higher education policy implications on the interactions among affirmative action bans, student racial diversity, and state political factors
Thesis(Master) -- KDI School: Master of Development Policy, 2024
Keywords: Education, Higher--United States; Affirmative action programs--Law and legislation--United States